Das spezifisch Christliche - allgemein menschlich? - Splett, Jörg (Zeitschrift für katholische Theologie, 2002)
According to W. Kern (1990) the "essence of Christianity" is in the same time also the core of humanity: i.e. charity. In this paper his thesis will be resumed and developed in respect to faith. To be a Christian means, that one confesses Jesus Christ as the Lord. This "particularity" however doesn't lack a common ground: Not alone charity is commonly human, but also the charity (of charity – 1 Cor 13) for the truth. Therewith the identity of the specific Christian and the essential human roots shows a double face. On the one hand the human love for truth acheaves its summet in Jesus, on the other hand Jesus is the answer to this searching love: "the truth bearing an human face".